UJI MEKANIK BENANG PLASTIK BERBAHAN DASAR POLIPROPILENA DAN CALPET SEBAGAI PENGUAT - Munasir, (Matematika dan Sains, 2009)
The aim of research was to describe the results of mechanical test to plastic string made from polypropilene and calpet. The plastic string was made using extruder machine with variety of temperature (H1-H10). To produce the plastic string that strong, though, and elongation not excess (>24%) needed calpet higher (6-7)% from PP and the high hoven (155-175 oC). From the mechanical test, the plastic string that made from the mixture of PP, calpet and coloring agent of 93%:7%; 94%:6%; 97,2%:2%:0,8% showed the tenacity of 5.1 g/D; 5.9g/D and 4.6 g/D, respectively. The though and strength of plastic string showed the highest value at the tenacity of 5.9 g/D and calpet concentration of 6%. oC). From the mechanical test, the plastic string that made from the mixture of PP, calpet and coloring agent of 93%:7%; 94%:6%; 97,2%:2%:0,8% showed the tenacity of 5.1 g/D; 5.9g/D and 4.6 g/D, respectively. The though and strength of plastic string showed the highest value at the tenacity of 5.9 g/D and calpet concentration of 6%.